Drug Resistance Analysis of Pathogens Isolated from Pediatric Patients in Mexico - Cruz-López, Flora; Rincón-Zuno, Joaquín; Morfin-Otero, Rayo; Rodríguez-Noriega, Eduardo; Corte-Rojas, Reyna Edith; Feliciano-Guzmán, José Manuel; Gil-Veloz, Mariana; Rodríguez-Muñoz, Lorena; Choy-Chang, Elena Victoria; Cetina-Umaña, Carlos Miguel; Avilés-Benítez, Laura Karina; Martínez-Meléndez, Adrián; López-Jácome, Esaú; Silva-Sánchez, Jesús; Bolado-Martínez, Enrique; López-García, Maribel; Castañeda-Duarte, Juan de Dios; Ramos-Medellin, Carmen Lucrecia; Escalante-Armenta, Samuel Pavel; Quintanilla-Cazares, Luis Javier; Couoh-May, Carlos Antonio; Quintana-Ponce, Sandra; Newton-Sánchez, Oscar Alberto; Rodriguez-Galicia, Verónica; López-López, Dulce María; Huirache-Villalobos, Guadalupe Soledad; Ramirez-Mis, Jose Luis; Rojas-Larios, Fabián; Guerrero-Nuñez, Arely Elizabeth; Zubiate-Tejada, Héctor Miguel; Duarte-Miranda, Lizbeth Soraya; Barroso-Herrera-y-Cairo, Irma Elena; Padilla-Rivas, Gerardo; Garza-González, Elvira (Journal of Pediatric Infectious Diseases, 2023)
Objective To analyze the resistance to antimicrobials in clinical isolates from pediatric patients in Mexico.Methods Susceptibility data from relevant specimens were collected in the pediatric population over 6 months from 25 centers from 17 states of Mexico and analyzed using the WHONET 5.6 software. Data were stratified into three age groups: younger than 2 years, 2 to 6 years, and 6 to 18 years.Results For Escherichia coli, the infant/toddler group had higher resistance rates to ampicillin, ampicillin-sulbactam, cefuroxime, cefepime, gentamicin, quinolones (p < 0.001), amoxicillin/clavulanic acid (p = 0.003), and ceftazidime (p = 0.004) than the other two age groups. Additionally, a high proportion of extended-spectrum β-lactamase (ESBL)-producing isolates for E. coli (75.3%) was detected in this age group. Comparable results were observed for Klebsiella pneumoniae, with higher resistance to ampicillin-sulbactam, ceftazidime, gentamicin, cefepime, trimethoprim-sulfamethoxazole, carbapenems (p = 0.001) and amoxicillin/clavulanic acid (p = 0.023) in the infant/toddler group. Moreover, a high proportion of ESBL producers (76%) was detected in this age group. Regarding wards, E. coli and K. pneumoniae had the highest carbapenem resistance in the ICU area, and Acinetobacter baumannii had the highest carbapenem resistance in medical wards.Conclusion High antibiotic resistance rates were detected in the infant/toddler group. This report presents baseline data for future prospective surveillance studies of antimicrobial resistance in pediatric patients in Mexico.
Keywords: antimicrobial resistance; methicillin-resistant; carbapenem-resistant Enterobacterales; pediatric patients